Non-English lecturers' perception and their difficulties toward English Proficiency Test (EPT) for lecturer certification - Fitria, Tira Nur (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2022)
The importance of English Proficiency Test (EPT) cannot be separated from the career development of lecturers in Indonesia, as it has become a requirement for obtaining the much desired lecturer certification. This research is conducted to find out the non-English lecturers' perceptions and difficulties with EPT. It employed a descriptive qualitative approach and used a questionnaire as the data collection method. The results show that non-English lecturers agree that EPT is a deserved requirement for lecturer certification. They were also in agreement with the certain passing grades in EPT, certain fees in EPT payment, the institutions which administer the EPT, and the scheduling of EPT. The study suggests that the case leans more towards the non-English lecturers' difficulties in doing the EPT which concern 1) the lack of preparation in the form of (both) offline and online courses, 2) difficulties in certain English skills, 3) the lack of English vocabularies, 8) the time limit of EPT, 4) the overwhelming number of questions, 5) unfamiliarity with the various types of questions, 6) the absence of clear guidelines in EPT, and 7) the lack of clear instructions for the test items. Furthermore, it was found that while the institution, faculty, or study program gives full support regarding policies and facilities in administering EPT courses for the lecturer certification, most of them do not provide the compensation for the lecturers who take the EPT.